Gestalt counseling application to resolve psychological disorder - Mutari, Harisila; Suranata, Kadek; Gading, Ketut (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
The impact of the COVID-19 pandemic on children in Indonesia is getting bigger and wider. Based on an analysis of various policy responses and research findings, it was found that one of the impacts caused by the pandemic was that it greatly impacted children's mental health. health protocols, most children have fear, anxiety, are starting to adapt to crowds of people because for almost a year they have only been undergoing the learning process online. Moreover, the impact caused by this virus is death. Gestalt therapy is a therapeutic approach used by many groups in their research. This approach is still rarely used in the school environment by counselors due to a lack of knowledge in using this Gestalt approach technique. The purpose of writing can provide information that the Gestalt approach with the techniques in it makes a good contribution in overcoming psychological disorders in children. The author uses the literature analysis method through Publish or Perish and uses VOS (Vos of viewers). This literature review has explored research on the benefits of the Gestalt approach for children. The results of using this literature analysis is that the Gestalt approach is beneficial for children, namely: emotional self-expression, conflict resolution, contact with therapists, well-being, self-esteem, communication skills and are useful in treating psychological disorders including reducing depression, child anxiety, parental anxiety, and symptoms of trauma and other psychological disorders. From the results of the literature review it shows that evidence of Gestalt interventions is effective in dealing with psychological disorders in children.